System dynamics approach in analyzing impact of demographic and salary risks on pension expenditure - Sapiri, Hasimah; Kamil, Anton Abdulbasah; Mat Tahar, Razman; Tumin, Hanafi (Academic Journals, 2011)
Public pension plan in Malaysia is studied to analyze pension expenditure due to salary and demographic risks. Through the literature review and interview session with several officers in public sector, factors affecting pension expenditure are determined.The System Dynamic model is later developed using iThink software to show how demographic and salary changes affect the pension expenditure. Then, by using actual data, the impact of demographic and salary risks on pension expenditure is analyzed. The dynamics simulation model developed in this paper offers a useful tool for analyzing pension expenditure as a result of demographic and salary risks.